TELAAH KRITIS PENGATURAN TENTANG YAYASAN DI INDONESIA - Fitriani Jamaluddin (IAIN Palopo, 2020)
The purpose of this study is to examine Law No. 16 of 2001 concerning Foundations in conjunction with Law No. 28 of 2004 concerning Foundations. The results showed that the basic purpose of establishing the foundation for social, humanitarian, and religious interests in implementation was not in accordance with the provisions of the Foundation Law, besides that there was no sanction for Foundation organs that took advantage of personal interests in the management of the Foundation.